Answer:
![(\frac{f}{g})(x)=\frac{1}{3}(x^2+3x+9)](https://tex.z-dn.net/?f=%28%5Cfrac%7Bf%7D%7Bg%7D%29%28x%29%3D%5Cfrac%7B1%7D%7B3%7D%28x%5E2%2B3x%2B9%29)
Step-by-step explanation:
We have been given that
![f(x)=x^3-27,g(x)=3x-9](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E3-27%2Cg%28x%29%3D3x-9)
We can use the formula for difference of cubes to simplify the function f(x)
difference of cubes - ![a^3-b^3=(a-b)(a^2+ab+b^2)](https://tex.z-dn.net/?f=a%5E3-b%5E3%3D%28a-b%29%28a%5E2%2Bab%2Bb%5E2%29)
![f(x)=x^3-27\\\\=x^3-3^3\\\\=(x-3)(x^2+3x+9)](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E3-27%5C%5C%5C%5C%3Dx%5E3-3%5E3%5C%5C%5C%5C%3D%28x-3%29%28x%5E2%2B3x%2B9%29)
And g(x) can be written as
![g(x)=3x-9\\=3(x-3)](https://tex.z-dn.net/?f=g%28x%29%3D3x-9%5C%5C%3D3%28x-3%29)
Thus, we have
![(\frac{f}{g})(x)=\frac{(x-3)(x^2+3x+9)}{3(x-3}](https://tex.z-dn.net/?f=%28%5Cfrac%7Bf%7D%7Bg%7D%29%28x%29%3D%5Cfrac%7B%28x-3%29%28x%5E2%2B3x%2B9%29%7D%7B3%28x-3%7D)
On cancelling the common factors, we get
![(\frac{f}{g})(x)=\frac{1}{3}(x^2+3x+9)](https://tex.z-dn.net/?f=%28%5Cfrac%7Bf%7D%7Bg%7D%29%28x%29%3D%5Cfrac%7B1%7D%7B3%7D%28x%5E2%2B3x%2B9%29)
Answer: 160
Step-by-step explanation: 5% of x = 8
In other words, x * 0.05 = 8. To find what x is, we need to work backwards.
x * 0.05 = 8
x = 8/0.05
x = 160
Would appreciate a brainly <3
9514 1404 393
Answer:
y = 4/5x +13/5
Step-by-step explanation:
The slope is given by the formula ...
m = (y2 -y1)/(x2 -x1)
m = (5 -1)/(3 -(-2)) = 4/5
The y-intercept is given by the formula ...
b = y -mx . . . . for any point (x, y)
b = 1 -(4/5)(-2) = 1 +8/5 = 13/5 . . . . using the first point
So, the equation is ...
y = mx +b
y = 4/5x +13/5
_____
<em>Additional comment</em>
If you have a bunch of these to do, you may want to make a spreadsheet with the formulas built in. Then you can type in the two points and have it spit out the m and b for your equation. Even if you don't use it to <em>do</em> the work, you can use it to <em>check</em> the work.
Answer:
B
Step-by-step explanation:
-8+2=-6 and im pretty sure negative of a power is just a regular power so its B
Answer:
The formula used to convert Fahrenheit in to Celsius is:
![C = ( F - 32) \times (\frac{5}{9})](https://tex.z-dn.net/?f=C%20%3D%20%28%20F%20-%2032%29%20%5Ctimes%20%28%5Cfrac%7B5%7D%7B9%7D%29)
Step-by-step explanation:
Here, the given expression is :
![F=(\frac{9}{5}) c + 32](https://tex.z-dn.net/?f=F%3D%28%5Cfrac%7B9%7D%7B5%7D%29%20c%20%2B%2032)
The above expression converts Celsius in to Fahrenheit.
Now we need an expression to convert Fahrenheit in to Celsius.
Simplifying the above for the value of C, we get:
![F=(\frac{9}{5}) c + 32\\\implies F - 32 =(\frac{9}{5}) c \\\implies ( F - 32) \times (\frac{5}{9}) = c\\\implies C = ( F - 32) \times (\frac{5}{9})](https://tex.z-dn.net/?f=F%3D%28%5Cfrac%7B9%7D%7B5%7D%29%20c%20%2B%2032%5C%5C%5Cimplies%20F%20-%2032%20%3D%28%5Cfrac%7B9%7D%7B5%7D%29%20c%20%5C%5C%5Cimplies%20%20%28%20F%20-%2032%29%20%5Ctimes%20%28%5Cfrac%7B5%7D%7B9%7D%29%20%20%20%3D%20c%5C%5C%5Cimplies%20C%20%3D%20%28%20F%20-%2032%29%20%5Ctimes%20%28%5Cfrac%7B5%7D%7B9%7D%29)
Hence, the formula used to convert Fahrenheit in to Celsius is:
![C = ( F - 32) \times (\frac{5}{9})](https://tex.z-dn.net/?f=C%20%3D%20%28%20F%20-%2032%29%20%5Ctimes%20%28%5Cfrac%7B5%7D%7B9%7D%29)